Investigation of the Relationship Between Health Promotion Behavior and Self-efficacy of Turkish Adolescents - Mehmet Coşgun; Kemal Macit Hisar (Genel Tıp Dergisi)
Purpose: This research was carried out to identify the relationship between adolescent health promotion behaviors and the self-efficacy of students. Materials and Method: This study is a descriptive study, which was carried out in a secondary school and two high schools in the provincial center of Ankara in the 2017-2018 academic year. Three different forms were used as data collection tools. These are questionnaire form, adolescent health promotion scale, and self-efficacy scale for children. The data were summarized as mean, standard deviation, and percentages. Results: In adolescent health promotion scale and all subscale scores, there were significant differences according to their class, age, success status, health state perception, beliefs in managing future health statuses, wearing a seat belt, wearing a helmet while riding a bicycle or motorbike, using pedestrian crossings and overpasses when crossing the road. In self-efficacy scale and all subscale scores, there were significant differences according to their class, age, success status, health state perception, beliefs in managing future health statuses, wearing a seat belt, wearing a helmet while riding a bicycle or motorbike, using pedestrian crossings, and overpasses when crossing the road. There was a positive and significant correlation between health-promoting behaviors and self-efficacy. Conclusions and Suggestions: Self-efficacy perception and health-promoting behaviors are gained during childhood and adolescence and maintained throughout life. For this reason, education, seminars, and activities to be given to students, teachers, and parents will be effective in increasing self-efficacy perceptions of adolescents and gaining health-promoting behaviors of adolescents.